Masyarakat dalam Mewujudkan Festival Atau Acara Religi yang Berkelanjutan: Studi Kasus di Indonesia - Mohammad Habibi Surya Buwana; Karin Sufi Permatasari; Bambang Suharto; Aurellya Rahmada Dewinta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Village engagement religious tourism is a form of cultural tourism that is attractive to domestic and foreign tourists. Indonesia has many villages that are rich in historical heritage and Islamic traditions, which are an attraction for religious tourism. The development of religious tourism villages does not only involve the government and tourism businesses, but also requires the participation of the local community. This study aims to analyse the role of community participation in the development of religious tourism villages in Indonesia. The method used is a qualitative approach with case studies on two religious tourism villages, namely Gantarang Lalang Bata Village in South Sulawesi and Koya Barat Village. Data collection was conducted through literature study. The results showed that community participation plays an important role in preserving culture and traditions, providing homestays and local culinary, becoming tour guides, being involved in decision-making and planning, providing crafts and souvenirs, and promoting religious tourism villages. Active community participation can ensure that the development of religious tourism villages is in line with the aspirations and values of the local community, and provides economic benefits to the community. This research provides an in-depth understanding of the importance of community participation in the development of sustainable religious tourism villages.